LEARNING MEDIA DEVELOPMENT OF THE GAME OF THE CROWN GAME IN THE CIVICS LESSON OF ELEMENTARY SCHOOL CLASS III - Raudhah Anisa Muslim; Munjiatun; Zariul Antosa (Education Generation Journal, 2023)
This research is motivated by the lack of learning media in the implementation of Civics learning, therefore the need for learning tools that support one of them is learning media. the media developed is interesting media, in accordance with the characteristics and needs of students. The purpose of this study was to determine the development and determine the feasibility of "Development of Learning Media for Snakes and Ladders Games in Primary Grade III Civics Subjects". The results of validation from experts state that the product "Development of Learning Media for Snakes and Ladders Games in Civics Subjects for Primary Grade III" is very feasible to use. The conclusion in this study based on the analysis of validators, teacher responses and student responses shows that the product "Development of Learning Media for Snakes and Ladders Games in Civics Subjects Elementary School Class III" developed by researchers is declared valid for use as a Civics learning media in Class III Elementary School.